Ion association of glycine, α-alanine and β-alanine in water and water+ D-glucose mixtures at different temperatures - Sanjibita Das and Upendra N. Dash (Journal of Applied Pharmaceutical Science, 2013)
The conductance of glycine, α-alanine and β-alanine has been measured in the concentration range of 1×10-2 to 8×10-2 mol dm-3 in aqueous and aqueous binary mixtures containing D-glucose (5,10,15,20% (w/w)) at different temperatures (298.15-313.15 K). The conductance data in all cases have been computed by Shedlovsky equation to obtain Λ0m and KA . Based upon the composition dependence of Walden product, the influence of the D-glucose mixtures on the solvation of ions has been discussed. The values of the association constants, KA, are used to obtain various thermodynamic parameters for the association process in the solution.
Keywords: Electrical conductivity, amino acids, D-glucose, ass